EFFECTIVENESS OF USING INTERNET TECHNOLOGY IN FINDING KNOWLEDGE AND SKILLS FOR PKBM LEARNING CITIZENS - Nunu Mahmud Firdaus; Babang Robandi (Journal Of Educational Experts (JEE), 2021)
Technology has a broad impact in various aspects of life, including major changes in the implementation of education, the demand is that education is able to produce human resources who have high competence, in the 21st century students are required to be able to learn through increasingly advanced and limitless technology. In the 21st century there is a very different process of absorbing information, which in the previous era, science produced advanced technology like today, the current pedagogical challenge is how technology can transfer knowledge to students. The world of education is required to be able to create education that produces complete Indonesian human resources who make a major contribution to building social and economic order in the 21st Century. The purpose of this study is to describe the 21st century information technology that continues to be developed in the world of education to make an educational revolution that uses technology as a source of information. The research method used is descriptive qualitative. The sample of this research is residents studying at PKBM Ibun in Bandung Majalaya district with 20 respondents. The results show that 21st century technology can transfer useful information and provide a lot of new knowledge, including skills and learning to innovate; (2) life and career; and (3) information technology and media skills.